Aspergillus Infection of the Thoracolumbar Vertebral Body in a Chronic Hepatitis B-Related Hepatocellular Carcinoma Patient: A Case Report. Issue 2 (8th June 2022) - Liu, Jing; Gao, Yi-Dan; Jiang, Yan-Ming; Wang, Jie; Li, Ge; Zhou, Xiang; Zhu, Qian-Ru; Chen, Gong-Ying
Abstract : This study reports a rare case of an Aspergillus infection of the thoracolumbar vertebral body in a chronic hepatitis B-related hepatocellular carcinoma patient. We report a hepatocellular carcinoma patient who presented with a 3-month history of lumbago after liver transcatheter arterial chemoembolization, and was finally diagnosed with a pulmonary and thoracolumbar vertebral body Aspergillus infection after diagnostic antifungal treatment for 1 year. This case suggests that diagnostic antifungal therapy is of great significance for patients with clinically suspected Aspergillus infections when it is difficult to obtain tissue specimens for determined diagnosis.